Comparison of in vivo confocal endomicroscopy with other diagnostic modalities to detect intracellular helicobacters. (July 2016) - Sharman, M.; Bacci, B.; Simpson, K.; Mansfield, C.
Highlights: Helicobacters are detected intracellularly, and might contribute to pathology, allow evasion therapy and perpetuate disease The role of gastric non- H. pylori helicobacters in dogs is unknown, but they may contribute to disease in some dogs. Confocal endomicroscopy (CEM) can detect H. pylori and other mucosally-associated and intracellular bacteria. CEM allows in vivo, dynamic and functional evaluation of the gastric mucosal morphology and detection of Helicobacter spp. Only Fluorescence in situ Hybridisation (FISH) allowed detection of an intracellular location. Abstract: Intracellular colonisation may serve as a protected niche where Helicobacter spp. organisms evade effective treatment. In dogs, non- Helicobacter pylori -helicobacters are frequently intracellular. Confocal endomicroscopy allows in vivo gastrointestinal imaging and has aided real-time identification of Helicobacter pylori and other intracellular and mucosally associated bacteria. The objectives of this study were: (1) to determine the utility of confocal endomicroscopy to identify non- Helicobacter pylori -helicobacters compared with other diagnostic modalities, and (2) to assess its ability to identify intracellular organisms. Fourteen clinically healthy dogs underwent standard gastroduodenoscopy followed by confocal endomicroscopy using topical acriflavine. Confocal images were obtained from at least five gastric sites. Endoscopic biopsies were obtained for histopathology, PCR and fluorescence in situ hybridisation (FISH). Methodologies were compared for their ability to determine the presence and spatial distribution of gastric helicobacters in dogs. Confocal endomicroscopy provided high quality images allowing in vivo identification of non- Helicobacter pylori -helicobacters in 13 dogs. Histopathology identified helicobacters in 11 dogs. Organisms were identified within the superficial gastric mucus and within gastric pits, and distribution throughout the stomach was diffuse and multi-focal. Confocal endomicroscopy findings correlated with PCR and FISH post-procedure analysis. Only FISH identified intracellular organisms, which were present in 13/14 dogs. Confocal endomicroscopy provided in vivo histology images and was capable of identifying non- Helicobacter pylori -helicobacters during gastroscopy, but was unable to identify intracellular organisms using the current fluorophore protocol.